2016
DOI: 10.1177/1071100716659747
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Related Normative Data for the Foot Function Index in a German-Speaking Cohort

Abstract: II, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
3
10
1
Order By: Relevance
“…Several foot- and ankle-specific scores are available, such as the Foot and Ankle Outcome Scale (FAOS), 32 the Manchester-Oxford Foot Questionnaire (MOXFQ), 10 the Foot Function Index (FFI), 33 the American Orthopaedic Foot & Ankle Society (AOFAS), 34 and the Low Extremity Functional Scale (LEFS). 12 However, to our knowledge, no population-based normative values are published for any of these.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several foot- and ankle-specific scores are available, such as the Foot and Ankle Outcome Scale (FAOS), 32 the Manchester-Oxford Foot Questionnaire (MOXFQ), 10 the Foot Function Index (FFI), 33 the American Orthopaedic Foot & Ankle Society (AOFAS), 34 and the Low Extremity Functional Scale (LEFS). 12 However, to our knowledge, no population-based normative values are published for any of these.…”
Section: Discussionmentioning
confidence: 99%
“…Normative values are missing for FAOS and MOXFQ, whereas FFI, AOFAS, and LEFS have normative values published, but based on examinations of volunteers such as hospital employees. 12,33,34 That is, our study provides the first population-based normative foot- and ankle-specific PROM values, reflecting the general population, with data collected in a similar way as for the generic scores SF-36 and EQ-5D. 16,17,19,24,25,36 By this approach, we found that SEFAS normative values correlated inversely with age, similar to what has been found for the PROMs FFI, AOFAS, and LEFS, 12,33,34 and that men have higher SEFAS values than women, similar to the scores SF-36, 19 AOFAS, 34 FFI, 33 and LEF.…”
Section: Discussionmentioning
confidence: 99%
“…For future studies, it is recommended that the responsiveness of this questionnaire should be evaluated, in order to determine whether this instrument is capable of detecting clinical changes in patients after a period of time and also, to identify the normative values of the FFI questionnaire in the Brazilian population. These values will contribute to the correct interpretation of the FFI scores according to the age, gender, and anthropometrics data, to allow the understanding of the clinical improvement after treatment in each evaluated group (Schneider and Jurenitsch 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Normative data for PROMs can aid in this problem by acting as reference data for a healthy population. Normative data are available for a few PROMs (Aasheim and Finsen 2014, Schneider and Jurenitsch 2016). For the LEFS, however, no such data are available.…”
mentioning
confidence: 99%